Effects of Periodization Core Training on Physical Fitness in College Table Tennis Players - Kuan Dong; Guyeol Jeong; Jing Tian; Buongo Chun (PLoS ONE, 2025)
Objective This study aimed to analyze the effects of 12-week periodized core training on the physical fitness of college table tennis players. Methods A randomized controlled experimental design was employed, and 18 college table tennis players (male = 11, female = 7) were randomly assigned to the core training group (CT, n = 9) and the control group (CON, n = 9). The core training group performed periodized core training for 12 weeks. All variables were assessed at three time points: pre-test, mid-test (after 9 weeks), and post-test. Results Significant interactions were found between time and group for muscle endurance, balance, and agility, as demonstrated in Left Side Bridge (p < 0.05), Right Side Bridge (p < 0.001), Plank (p < 0.01), and Edgren Side Step (p < 0.001). However, no significant interactions were observed for speed, muscle strength, or power. Conclusion Periodized core training has a positive effect on the muscle endurance, agility, and balance of college table tennis players. The improvement in agility may be attributed to the integration of sport-specific periodized training. Further research is required to examine its effects on speed and anaerobic capacity. Periodized core training appears to have limited effects on strength and power, suggesting it can be used as a supplementary element within a comprehensive training program to enhance physical fitness and performance among college table tennis players.